Self Value dalam Bayang-Bayang Uang: Kajian Hadis ‘Abd al-D?n?r’ dan Perspektif Filsafat Sosial Kontemporer - Yusi Fathurohman; Salsabila Alifiya; Abdul Aziz; Andi Rosa (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2025)
This paper discusses the phenomenon of a self-value crisis in the context of modern materialism, with a focus on the Prophet Muhammad’s ?ad?th concerning ‘abd al-d?n?r (the slave of money). The study integrates a ?ad?th-based approach with contemporary social philosophy to understand the impact of monetary domination on individual identity and morality. The findings reveal that the ?ad?th offers a profound critique of material enslavement, while social philosophy highlights the structural mechanisms that reinforce consumerist culture. This paper recommends a renewal of spiritual and social consciousness as an effort to restore authentic self-value